Supervision as a Solution to Improve Hand Hygiene Compliance - Ayu, Jennyla Puspitaning (Fakultas Kedokteran Universitas Brawijaya, 2021)
Hand hygiene is an act to prevent and control infections, one of which is nosocomial phlebitis infection. The results of a preliminary study conducted at Syuhada Haji Hospital Blitar showed the number of phlebitis cases had not reached the target of â‰¤1.5% (1.63% in December 2018). One of the reasons was hand hygiene non-compliance. This study intended to analyze the factors causing non-compliance with hand hygiene in Syuhada Haji Hospital Blitar and find alternative solutions. This study was a case study conducted with observations on implementing nurses in five inpatient rooms and Focus Group Discussion (FGD) on five implementing nurses and eight management staff at Syuhada Haji Hospital Blitar. The main factor influencing compliance with hand hygiene at Syuhada Haji Hospital is that no supervision policy supports hand hygiene implementation, and the solution is supervision for monitoring hand hygiene compliance. Supervision is expected to increase compliance and awareness of the importance of hand hygiene; thus, in turn, affect the service quality.